Exploring the Factors Affecting Students’ Choice of Higher Education Institutes in India: A Factor Analysis Approach - Rajput, Gaurav; Chouhan, Preeti Singh (Journal of Business and Social Sciences Research, 2021)
The study seeks to identify and explore those factors the students consider while selecting a higher education institute or a university. The study is based on quantitative data as well as qualitative data. Individual interviews were conducted with subject experts and students. The data for analysis was collected from 212 students of the Indore region by using a structured questionnaire and judgemental sampling technique. With the help of exploratory study discovered eight factors were analysed namely– past placement record and programme design, college working hours and well-resourced library, co-curricular activities and alumni feedback, faculty expertise, benefits and expenditure, state-of-the-art, supportive staff, and additional facilities; that are considered while choosing a higher education institute. These eight factors were further examined through a confirmatory factor analysis to confirm the proposed model. An eight-factor model consisting of the factors affecting the students’ choice of higher education institutes.